نحو تفعيل طرق التدريس في التعليم الجامعي، طريقة المحاضرة أنموذجا - الدكتورة كحول, شفيقة; الدكتورة غربي, صباح (دفـاتر المـــــــــــخبـر, 2018)
الملخص     للعملية التعليمية مكونات اساسية تجعلها تصل الى اهدافها واهمها تبليغ المعرفة للمتعلمين، وهذه المكونات هي الاهداف (الكفاءات)، المحتوى التعليمي، الطرائق التدريسية والوسائل التعليمية، وفي الاخير تأتي عملية التقويم التربوي.     يأتي هذا العمل ليتناول مكون طرائق التدريس التي تعد الاسلوب أو الكيفية التي تقدم وفقها المحتويات، لتوجه نشاط المتعلم نحو الاهداف التعليمية، ويختص بطريقة قديمة –حديثة، ألا وهي طريقة المحاضرة التي تنتشر بكثرة في التعليم الجامعي، ويسعى الى اقتراح جملة من المعايير التي من شأنها أن تفعل منها وتجعلها أكثر فعالية. Abstract:    The educational process has basic components that make it reach its goals and the most important is to inform the learners. These components are the goals (competencies), the educational content, the teaching methods and the teaching aids. This work comes to deal with the component of teaching methods, which is the method or how to provide the contents, to direct the learner's activity towards educational goals, and specializes in an old - modern, the method of lecture, which is widespread in university education, and seeks to propose a set of criteria that would To do them and make them more effective.